Clinical study on the selection of endoscopes and microscopes for transsphenoidal surgery of non-aggressive pituitary macroadenoma and microadenoma and the influencing factors of hyposmia after endoscopic transsphenoidal surgery - Kong, Fanyi; Cheng, Weiping; Zhan, Qingyang (Frontiers in Neurology, 2024)
Background and objective Transsphenoidal surgery, including endoscopic and microscopic resection, is the first choice of treatment for pituitary tumors. With the widespread application of neuroendoscopy in recent decades, there has been a trend to replace microscopes. In clinical practice, we have found that in transsphenoidal surgery for non-invasive microadenomas and macroadenomas, microscopy can achieve a higher total resection rate, shorter operation time, lower incidence of postoperative complications, and faster recovery of olfaction. This study aimed to explore the selection of endoscopes and microscopes for non-aggressive transsphenoidal surgery for pituitary adenomas and the factors affecting olfactory recovery. Methods From August 2019 to October 2022, 93 patients with non-aggressive microadenomas and macroadenomas via the transsphenoidal approach were selected from the First Affiliated Hospital of Harbin Medical University and treated with rich experience in pituitary tumor subspecialty microscopy and endoscopic surgery. Different surgical methods were used to divide the patients into microscopic (n = 35) and endoscopic (n = 58) groups. The total tumor removal rate, intraoperative blood loss, operation time and cost, postoperative hospital stay, recovery of visual function, postoperative changes in hormone levels, complication rate, and recovery from complications 3 months after the operation were compared between the two groups. Results There were no significant differences in the tumor removal rate, postoperative visual acuity, and visual field recovery between the two groups (p > 0.05). There was a significant difference in the recovery rate of olfactory function between the two groups 3 months after the operation (p < 0.05), and there was no significant difference in the incidence of other complications (p > 0.05); Compared with the two groups, the microscope group had shorter operation time, longer postoperative hospital stay, less average operation cost and less blood loss, and the difference was statistically significant (p < 0.05). The position of the nasal septum mucosal flap incision was a risk factor for hyposmia 3 months after the operation. Conclusion Microsurgery and endoscopic surgery are suitable surgical treatments for nonaggressive microadenomas and macroadenomas. The total tumor removal and postoperative hormone remission rates of the two surgical methods were approximately the same. However, the microsurgery group had a shorter operation time, less intraoperative blood loss, faster olfactory function recovery, and a lower average operation cost. The position of the nasal septal mucosal flap incision was a risk factor for hyposmia at 3 months postoperatively. Hyposmia is less likely to occur when the superior edge of the nasal septal mucosal flap incision is not higher than the lower edge of the ipsilateral superior turbinate.